2015
DOI: 10.1016/j.frl.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Does gender diverse board mean less earnings management?

Abstract: Available online xxxx JEL classification: G34 J16 M10 M41 a b s t r a c tWe examine the effect board gender diversity has on earnings management in European countries. The findings reveal that a gender diverse board mitigates earnings management in countries where gender equality is high. This provides an explanation to the inconclusive findings in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 17 publications
14
69
1
10
Order By: Relevance
“…Hypothesis 1 that proposed the negative effect of women in top supervisory on earnings management characterized women as more conservative in financial reporting, therefore the earning quality in financial statements could be supported with empirical data. The findings were aligned with previous research by Kyaw, Olugbode, & Petracci (2015) who described the negative significant effect of women on top supervisory toward earnings management. Liu, Wei, & Xie (2016) | 574 | earnings management and women in top supervisory.…”
Section: Women In Top Supervisorysupporting
confidence: 89%
“…Hypothesis 1 that proposed the negative effect of women in top supervisory on earnings management characterized women as more conservative in financial reporting, therefore the earning quality in financial statements could be supported with empirical data. The findings were aligned with previous research by Kyaw, Olugbode, & Petracci (2015) who described the negative significant effect of women on top supervisory toward earnings management. Liu, Wei, & Xie (2016) | 574 | earnings management and women in top supervisory.…”
Section: Women In Top Supervisorysupporting
confidence: 89%
“…A study by Arun, Almahrog, and Aribi (2015) showed that UK companies with higher number of independent female directors on the corporate board, have reduced earnings management practices. On top of that, Kyaw, Olugbode, and Petracci (2015) also presented similar result among European countries with high gender equality.…”
Section: Asian Journal Of Finance and Accountingsupporting
confidence: 63%
“…A number of firm-specific control variables included in the study are based on the existing literature (Amran, Ishak, and Abdul Manaf, 2016;Chandren et al, 2015;Kyaw, Olugbode, and Petracci, 2015). Specifically, firm growth shows that there is no relationship with real earnings management at a coefficient of 0.0620.…”
Section: Resultsmentioning
confidence: 99%